Using stable isotopes to inform water resource management in forested and agricultural ecosystems - Scandellari, Francesca; Attou, Taha; Barbeta, Adrià; Bernhard, Fabian; D'Amato, Concetta; Dimitrova-Petrova, Katya; Donaldson, Amanda; Durodola, Oludare; Ferraris, Stefano; Floriancic, Marius G; Fontenla-Razzetto, Gabriela; Gerchow, Malkin; et al. (Journal of environmental management, 2024)
Present and future climatic trends are expected to markedly alter water fluxes and stores in the hydrologic cycle. In addition, water demand continues to grow due to increased human use and a growing population. Sustainably managing water resources requires a thorough understanding of water storage and flow in natural, agricultural, and urban ecosystems. Measurements of stable isotopes of water (hydrogen and oxygen) in the water cycle (atmosphere, soils, plants, surface water, and groundwater) can provide information on the transport pathways, sourcing, dynamics, ages, and storage pools of water that is difficult to obtain with other techniques. However, the potential of these techniques for practical questions has not been fully exploited yet. Here, we outline the benefits and limitations of potential applications of stable isotope methods useful to water managers, farmers, and other stakeholders. We also describe several case studies demonstrating how stable isotopes of water can support water management decision-making. Finally, we propose a workflow that guides users through a sequence of decisions required to apply stable isotope methods to examples of water management issues. We call for ongoing dialogue and a stronger connection between water management stakeholders and water stable isotope practitioners to identify the most pressing issues and develop best-practice guidelines to apply these techniques.
Keywords: Climate change; Forests; ochrana vodních zdrojů; vodní zdroje; zemědělství; lesy; Water Resources; Isotopes; Forest management; podzemní voda; Stable isotopes of water; Groundwater; izotopy; Conservation of Water Resources; Agricultural management; ekosystém; Water resources management; Ecosystem; Stakeholders; Agriculture